Controlled attenuation parameter and alcoholic hepatic steatosis: diagnostic accuracy and role of alcohol detoxification - Thiele, Maja; Rausch, Vanessa; Fluhr, Gabriele; Piecha, Felix; Müller, Johannes; Seitz, Helmut K.; Mueller, Sebastian (Journal of hepatology, 2018)
Background & Aims - Controlled attenuation parameter (CAP) is a novel non-invasive measure of hepatic steatosis, but it has not been evaluated in alcoholic liver disease. Therefore, we aimed to validate CAP for the assessment of biopsy-verified alcoholic steatosis and to study the effect of alcohol detoxification on CAP. - Methods - This was a cross-sectional biopsy-controlled diagnostic study in four European liver centres. Consecutive alcohol-overusing patients underwent concomitant CAP, regular ultrasound, and liver biopsy. In addition, we measured CAP before and after admission for detoxification in a separate single-centre cohort. - Results - A total of 562 patients were included in the study: 269 patients in the diagnostic cohort with steatosis scores S0, S1, S2, and S3=77 (28%), 94 (35%), 64 (24%), and 34 (13%), respectively. CAP diagnosed any steatosis and moderate steatosis with fair accuracy (area under the receiver operating characteristic curve [AUC] ≥S1=0.77; 0.71-0.83 and AUC ≥S2=0.78; 0.72-0.83), and severe steatosis with good accuracy (AUC S3=0.82; 0.75-0.88). CAP was superior to bright liver echo pattern by regular ultrasound. CAP above 290dB/m ruled in any steatosis with 88% specificity and 92% positive predictive value, while CAP below 220dB/m ruled out steatosis with 90% sensitivity, but 62% negative predictive value. In the 293 patients who were admitted 6.3days (interquartile range 4-6) for detoxification, CAP decreased by 32±47dB/m (p<0.001). Body mass index predicted higher CAP in both cohorts, irrespective of drinking pattern. Obese patients with body mass index ≥30kg/m2 had a significantly higher CAP, which did not decrease significantly during detoxification. - Conclusions - CAP has a good diagnostic accuracy for diagnosing severe alcoholic liver steatosis and can be used to rule in any steatosis. In non-obese but not in obese, patients, CAP rapidly declines after alcohol withdrawal. - Lay summary - CAP is a new ultrasound-based technique for measuring fat content in the liver, but has never been tested for fatty liver caused by alcohol. Herein, we examined 562 patients in a multicentre setting. We show that CAP highly correlates with liver fat, and patients with a CAP value above 290dB/m were highly likely to have more than 5% fat in their livers, determined by liver biopsy. CAP was also better than regular ultrasound for determining the severity of alcoholic fatty-liver disease. Finally, we show that three in four (non-obese) patients rapidly decrease in CAP after short-term alcohol withdrawal. In contrast, obese alcohol-overusing patients were more likely to have higher CAP values than lean patients, irrespective of drinking.
Gesehen am 06.08.2019